Best Practices for Building and Supporting Effective ACGME-Mandated Program Evaluation Committees - Jessica Greenfield; Elias I. Traboulsi; Krista Lombardo-Klefos; S. Beth Bierer (Association of American Medical Colleges, 2020)
Introduction The Accreditation Council for Graduate Medical Education (ACGME) mandates that residency training programs form program evaluation committees (PECs) to monitor program delivery and outcomes, generate annual program evaluations (APEs), facilitate strategic planning, and implement continuous quality improvement projects. Though PECs provide essential documentation to position programs for successful accreditation decisions, few resources exist in the literature for PEC members. Methods Employing Kern's model for curriculum development, we conducted a needs assessment in 2016 that resulted in adding a 2-hour workshop on building and supporting effective PECs to a certificate program for residency program directors. The workshop used a flipped classroom model with prework readings and guiding questions to familiarize participants with ACGME requirements for PECs and APEs. Several activities helped participants identify best practices for PECs and discuss authentic examples of mission statements, APEs, and action plans. Results From 2017 to 2019, we offered this workshop on three different occasions to a total of 42 participants (34 residency program directors/associate program directors and eight program coordinators). In 2019, 14 participants completed a web-based evaluation after the session. All agreed or strongly agreed that the workshop met the learning objectives, utilized interactive teaching methods, included useful APE examples, and provided valuable resources. Discussion This workshop addresses a gap in the literature by helping program directors identify best practices for PECs. The APE template and workshop examples can be adjusted to fit the needs of individual institutions.